Preparing Pharmacists for Collaborative/Integrated Health Settings - Frank J. Ascione (MDPI AG, 2019)
Pharmacy practice is changing to accommodate the need for pharmacists to be better team members in newly emerging collaborative care and integrated health systems. Pharmacy schools could lead this change by educating students to be effective participants in these relatively new models of care. Schools are encouraged to follow the approach outlined in the recent guidance published by the Health Professions Accreditors Collaborative (HPAC) for interprofessional practice and education (“the new IPE”). This approach includes articulating an IPE plan, establishing goals, assessing student achievement of the necessary IPE competencies, developing educational plans that are multi-faceted and longitudinal, and modifying the existing assessment/evaluation process to ensure the quality of the IPE effort. These curricular decisions should be based on existing and new research on the effectiveness of IPE on student’s attitudes, knowledge, skills, and behavior. A key decision is how to create effective interactions between pharmacy students and those of other professions. Educational emphasis should be directed toward team building skills, not just individual competencies. The pharmacy faculty probably need to enhance their teaching abilities to accommodate this change, such as learning new technology (e.g., simulations, managing online exchanges) and demonstrating a willingness to teach students from other professions.